Seizure characteristics and the use of anti-epileptic drugs in children and young people with brain tumours and epileptic seizures: Analysis of regional paediatric cancer service population. - Pilotto, Chiara; Liu, Jo-Fen; Walker, David A.; Whitehouse, William P. (Elsevier, 2018)
Purpose: Epileptic seizures complicate the management of childhood brain tumours. There are no published standards for clinical practice concerning risk factors, treatment selection or strategies to withdraw treatment with antiepileptic drugs (AED).